2019
DOI: 10.1162/jocn_a_01456
|View full text |Cite
|
Sign up to set email alerts
|

Action Intention-based and Stimulus Regularity-based Predictions: Same or Different?

Abstract: We act on the environment to produce desired effects, but we also adapt to the environmental demands by learning what to expect next, based on experience: How do action-based predictions and sensory predictions relate to each other? We explore this by implementing a self-generation oddball paradigm, where participants performed random sequences of left and right button presses to produce frequent standard and rare deviant tones. By manipulating the action–tone association as well as the likelihood of a button … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 51 publications
6
35
1
Order By: Relevance
“…Specifically, because the first sequence tone was a different frequency than the four preceding pacing tones, ERP amplitudes elicited by the first sequence tone could potentially reflect a mismatch negativity (MMN), which overlaps in time with both the N1 and the P2 (Näätänen, Paavilainen, Rinne, & Alho, 2007). In line with this, recent research suggests that predictions based on self-produced actions contribute to the MMN (Korka, Schröger, & Widmann, 2019). However, we suggest two reasons why an MMN is unlikely to account for self-specific P2 attenuation in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, because the first sequence tone was a different frequency than the four preceding pacing tones, ERP amplitudes elicited by the first sequence tone could potentially reflect a mismatch negativity (MMN), which overlaps in time with both the N1 and the P2 (Näätänen, Paavilainen, Rinne, & Alho, 2007). In line with this, recent research suggests that predictions based on self-produced actions contribute to the MMN (Korka, Schröger, & Widmann, 2019). However, we suggest two reasons why an MMN is unlikely to account for self-specific P2 attenuation in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…The Bayes factor (BF 10 ) was calculated using 10.000 Monte-Carlo sampling iterations; the null hypothesis corresponded to a standardized effect size δ = 0, while the alternative hypothesis was defined as a Cauchy prior distribution centred around 0 with a scaling factor of r = 0.707 (Rouder, Morey, Speckman, & Province, 2012). In line with the Bayes factor interpretation (Jeffreys, 1961;Lee & Wagenmakers, 2013) and with previous studies reporting Bayes factors (Korka et al, 2019;Marzecová et al, 2018;Stuckenberg, Schröger, & Widmann, 2019), data were taken as moderate evidence for the alternative (or null) hypothesis if the BF 10 was greater than 3 (or lower than 0.33), while values close to 1 were considered only weakly informative. Values greater than 10 (or smaller than 0.1) were considered strong evidence for the alternative (or null) hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many action‐effect studies failed to distinguish between the effects of overall probability vs. action intention. That is, even though the role of action intention as a main source of information driving predictions has been previously discussed in the literature (Hughes et al, 2013b; Waszak & Herwig, 2007), only recently did a study point out that the its effects on early sensory processing can be observed without global regularity of the standard tone (Korka et al, 2019). From this perspective, the present results are especially illustrative; here, the omission‐related activity likely represents the endogenous neural signature of prediction (Arnal & Giraud, 2012) that appears to be exclusively based on intention and specific action‐effect couplings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this goal in mind, Korka et al (2019) asked participants to make left and right key presses to generate high and low frequency tones. Based on the key-tone associations, but also on the ratio of left and right key press, they contrasted in three conditions predictions based on tone regularity, action intention, or both combined.…”
Section: Preattentional Processing Levels: the Intention-based Mmnmentioning
confidence: 99%